Employment preference for university of fresh engineering graduates - Yuzainee M.Y.; Rahmat R.A.O.K.; Zaharim A. (IEEE Computer Society, 2023)
The purpose of this paper is to examine whether university background significantly influences employers' views in selecting a new engineer in Malaysia industries. This paper briefly presents the employers' preference for university of engineering graduates. A questionnaire was used to collect data from 301 employers of Malaysian industries and the respondents were restricted to personnel at the higher rank position in engineering industries at Kelang Valley, Malaysia. However, the sample size was small and derived from engineering industries around the Kelang Valley and nearby only. The result indicates that the university background and record were found to significantly affect employers' views on preferences for graduates in job selection. Although accredited universities may not be a primary factor that drew the employers to prioritise their selection, they did not in any way disregard the importance of 'well-known university' and Tier category in SETARA obtains by the university. The university should therefore not underestimate the significance of their popularity and the Tier category exercised by Higher Education Institutions in Malaysia. The study shows the university needs to look into their images as well as their graduates' achievement after graduating and minimised any false impression about the image of their graduates. More research should be carried out on employers from other Malaysian industries before any generalisation can be made with any degree of confidence. Future study can also investigate the reasons behind the perception uncovered among the employers for a better understanding of their views. 2013 IEEE.